Management of Ossa Cruris radiographic technique with fracture cases at the Radiology Installation of Dr AK Gani Hospital Palembang - Sutanto, Ronny (JOURNAL OF HEALTH SCIENCE, 2024)
The ossa cruris is commonly called the lower leg, in the lower leg there are two bones, namely the tibia and fibula bones, the tibia or shin bone is the main skeleton of the lower leg and is located medial to the fibula or calf bone. cruris with a case of cruris fracture in the radiology department of the hospital. Dr. Ak Gani Palembang. There are two projections in the ossa cruris technique examination, namely AP and Lateral projections, the patient's position is sitting or lying supine on the examination table. Examination of the ossa cruris does not require too much equipment, including radiology apparatus, cassette and film with a size of 30 x 40 cm which is divided in half and a marker. To get a good radiographic picture in fracture cases, efforts are made, including: The patient must be comfortable and not increase the patient's pain. Choosing the right exposure factor in order to get optimal photo results, so that the optimal image is obtained so that it can provide information to establish a diagnosis. Based on the results of the radiographic examination of the ossa cruris with fracture cases at the Dr. Hospital Installation. Ak. Gani Palembang obtained photos: in the form of disturbance sublocations on Ro Cruris Dextra AP/Lat and object position, image density, image contrast and image sharpness on the ossa cruris radiographic technique with fracture cases in the AP and lateral positions have been declared good. Key words : Ossa Cruris radiography, Fracture